2021
DOI: 10.1177/15266028211058686
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Early and Mid-Term Outcomes After Fenestrated-Branched Endovascular Aortic Repair in Patients With or Without Prior Infrarenal Repair

Abstract: Objective: The purpose of this study was to compare short- and mid-term outcomes of fenestrated-branched endovascular repair (F-BEVAR) of pararenal (PRAA)/thoracoabdominal (TAAA) aortic aneurysms in patients with or without prior endovascular/open (EVAR/OAR) infrarenal aortic repair. Methods: Data from consecutive F-BEVAR (2010–2019) at two high-volume aortic centers were retrospectively reviewed. Primary endpoints were technical success, 30-day mortality, and overall survival. Secondary endpoints included 30-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Fenestrated-branched EVAR (F-B/EVAR) moves the proximal zone above the renal-visceral vessel where the native aorta is less prone to dilation and it may represent a feasible and safe alternative to EVAR in the case of hostile neck, especially for patients unfit for open surgical repair or for those with long life expectancy [ 38 ]. According to the outcomes of high-volume aortic centers, F-B/EVAR may be also proposed as the first-line approach in the case of proximal complication after EVAR, with satisfactory clinical outcomes comparable with patients undergoing treatment for native aneurysm [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fenestrated-branched EVAR (F-B/EVAR) moves the proximal zone above the renal-visceral vessel where the native aorta is less prone to dilation and it may represent a feasible and safe alternative to EVAR in the case of hostile neck, especially for patients unfit for open surgical repair or for those with long life expectancy [ 38 ]. According to the outcomes of high-volume aortic centers, F-B/EVAR may be also proposed as the first-line approach in the case of proximal complication after EVAR, with satisfactory clinical outcomes comparable with patients undergoing treatment for native aneurysm [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increased rate of target vessel-related endoleaks was found in patients with a prior repair in this study. However, this increase did not correlate with higher rates of reinterventions or lower primary patency at 5-year follow-up [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Still, the chronic nature of aneurysmal disease can contribute to the appearance of late aortic complications such as para-anastomotic aneurysms (PAA) and progression of disease with dilatation of the proximal aorta. Both clinical situations are challenging as they frequently involve the pararenal/paravisceral aorta and often occur in patients that are older and present more comorbidities than those treated for a primary AAA [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that fenestration and chimney techniques may be feasible for treating some aortic arch pathologies while preserving the blood supply of the brain and upper extremities in selected patients ( 22 ). However, the incidence of intraoperative endoleaks and the risk of cerebral infarction were underestimated for the chimney technique ( 23 ), especially in cases with an entry tear located very close to the beginning of branch arteries.…”
Section: Discussionmentioning
confidence: 99%